The Influence of Organizational Culture and Social Capital to Improve Employee performance - Noerchoidah; Yanus Sumitro (Journal of Economy, Accounting and Management Science (JEAMS), 2020)
This study aims to examine the influence of organizational culture and social capital on employee performance. The method used in this research is explanatory research with a quantitative approach. The sample used was 110 respondents. The sampling technique used was purposive sampling. Analysis of the data used in this study using descriptive statistics and the SPSS program. The results showed that organizational culture has a positive and significant effect on employee performance, and social capital has a positive and significant effect on employee performance. Organizational culture and social capital simultaneously have a positive and significant effect on employee performance.